PENGEMBANGAN INDUSTRI KECIL TAHU PADA SENTRAL INDUSTRI TAHU DAN TEMPE DESA SEPANDE KECAMATAN CANDI KABUPATEN SIDOARJO - RAKHMAN HOLLE, FAJRUR (Jurnal Pendidikan Ekonomi (JUPE), 2014)
Small industries soybean stand out in the sepande village of 1999 and prospects for the development of small industries soybean quite well, this is evidenced by the industry still goes out until now. However, the development of small industries soybean in sepande village until now is not maximized, since the passage of small industries soybean not accompanied by the addition quantity of production so that production is not increased. With the use of high quality raw materials, fuel available and the technology development of small industry should know more signifikant. This study was conducted to determine the development of small industries soybean in depande village candi subdistrict didoarjo regency. In this research uses descriptive research with a qualitative approach, so that the results of the research will be described and analyzed in accordance with the conditions or circumstances that occur in the field. Data collection techniques used include: 1) Observation informant, 2) Interview, 3) Documentation. Based on the research result shows that: the small industries soybean stands out in the s epande village from 1999 to the present. Developing small industries soybean because of the experienced human resources, the use of high quality raw materials, availability of fuel, and the availability of boiler technology. With the availability of boiler technology entrepreneurs began to leave the traditional production process. It is very helpful to know the process of the production of small industries in the Sepande village due to the use of technology can increase the quantity of production small industries soybean. By utilizing experienced human resources and labor entrepreneurs small industries soybean to solve problems and make decisions for the current production of raw material price increases. With raw material of very, fuel available, and the use of technology in the production of steam out the need for improvement and repair of production equipment production environment so as to improve the development of the small industries soybean. With the development of small industries know can provide benefits to the entrepreneurs know that it can increase the quantity of production out of the increase in the quantity of income entrepreneurs small industries soybean will grow. Keywords: Development, soybean industry, production Industri kecil tahu di Desa Sepande berdiri dari tahun 1999 dan prospek berkembangnya industri tahu cukup baik, hal ini dibuktikan dengan masih berjalannya industri tahu hingga sekarang. Akan tetapi pengembangan industri kecil tahu di Desa Sepande sampai sekarang belum maksimal, karena berjalannya industri tahu tidak diiringi dengan penambahan kuantitas produksi sehingga hasil produksi tidak bertambah. Dengan adanya pemanfaatan bahan baku yang berkualitas, bahan bakar yang tersedia dan teknologi seharusnya pengembangan industri kecil tahu lebih signifikant. Penelitian ini dilakukan untuk mengetahui pengembangan produksi industri kecil tahu di Desa Sepande Kecamatan Candi Kabupaten Sidoarjo. Dalam penelitian ini menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif, sehingga hasil penelitian akan diuraikan dan dianalisis sesuai dengan kondisi atau keadaan yang terjadi di lapangan. Teknik pengumpulan data yang digunakan antara lain: 1) Observasi Informan, 2) Wawancara, 3) Dokumentasi. Berdasarkan hasil penelitian diketahui bahwa : industri tahu di Desa Sepande berdiri dari tahun 1999 hingga sekarang. Industri kecil tahu berkembang karena adanya sumber daya manusia yang berpengalaman, penggunaan bahan baku yang berkualitas, ketersediaan bahan bakar, dan ketersediaan teknologi ketel uap. Dengan tersedianya tekhnologi ketel uap para pengusaha mulai meninggalkan proses produksi secara tradisional. Hal ini sangat membantu proses produksi indutri kecil tahu tahu di Desa Sepande karena penggunaan tekhnologi dapat menambah kuantitas produksi industri kecil tahu. Dengan memanfaatkan sumber daya manusia yang berpengalaman pengusaha tahu dan tenaga kerja untuk mengatasi masalah dan mengambil keputusan untuk produksi saat kenaikan harga bahan baku. Dengan bahan baku yang berkulitas, bahan bakar yang tersedia, dan penggunaan tekhnologi ketel uap dalam produksi tahu perlu adanya perbaikan peralatan produksi serta perbaikan lingkungan produksi sehingga dapat meningkatkan pengembangan industri tahu. Dengan adanya pengembangan industri kecil tahu dapat memberikan manfaat pada pengusaha tahu yaitu dapat menambah kuantitas produksi tahu dari bertambahnya kuantitas pendapatan pengusaha tahu akan bertambah. Kata kunci: Pengembangan, industri tahu, produksi.